2019
DOI: 10.1111/jdi.13031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobile phone application combined with or without self‐monitoring of blood glucose on glycemic control in patients with diabetes: A randomized controlled trial

Abstract: Aims/Introduction There is potential for mobile applications to deliver new self‐management interventions for chronic disease, especially in diabetes. The aim of the present study was to evaluate the effects of a mobile phone application (MPA) combined with or without self‐monitoring of blood glucose (SMBG) on glycemic control in patients with diabetes. Materials and Methods The study was a 24‐week period, four‐arm parallel group, non‐blinded, randomized trial. A total of 185 patients with mean age of 52 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 25 publications
5
36
0
2
Order By: Relevance
“…A phone-based treatment and behavioral coaching intervention also improved HbA 1c levels [ 15 ]. A similar improvement in HbA 1c control for type 2 diabetes was seen with another mobile-based intervention [ 16 ]. The addition of a tailored mobile coaching system for patients with diabetes showed reduced HbA 1c levels and improved diabetes self-management; the results were reproducible and durable [ 17 ].…”
Section: Introductionsupporting
confidence: 54%
“…A phone-based treatment and behavioral coaching intervention also improved HbA 1c levels [ 15 ]. A similar improvement in HbA 1c control for type 2 diabetes was seen with another mobile-based intervention [ 16 ]. The addition of a tailored mobile coaching system for patients with diabetes showed reduced HbA 1c levels and improved diabetes self-management; the results were reproducible and durable [ 17 ].…”
Section: Introductionsupporting
confidence: 54%
“…The TyG index has been validated as a screening tool for IR in non-rheumatic populations. This surrogate index has been used as a screen for IR in diabetic and non-diabetic Mexican populations [1416], and it has been implemented by researchers in several countries [17, 18]. Using HOMA-IR as the gold standard, the TyG index has a sensitivity of 84% and a positive predictive value of 81% for IR [16].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes-Carer for patients consists of four main parts: diabetic education, self management,patient community, and real-time communication between patients and clinicians and the result HbA1c levels in patients of all groups decreased significantly from baseline. There were significant differences in the proportions of patients that achieved HbA1c<7% between groups, especially in intervention group for six months duration of study in Shanghai (Yu & Yan, 2019). Welltang is a smart phone-based diabetes management application, which can be used by both patientsand clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…According to (Yu & Yan, 2019) study in outpatient department of Shanghai East Hospital with 185 participant showed that The Diabetes-Carer application, a mobile phonebased diabetes management platform, which can be used by both patients and clinicians. Diabetes-Carer for patients consists of four main parts: diabetic education, self management, patient community, and realtime communication between patients and clinicians and HbA1c levels in patients of all groups decreased significantly from baseline.…”
Section: Study Outcomesmentioning
confidence: 99%